2019
DOI: 10.1038/s41556-019-0348-8
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Rho–GDP directly activates mTORC2 kinase towards AKT through dimerization with Ras–GTP to regulate cell migration

Abstract: mTORC2 plays critical roles in metabolism, cell survival, and actin cytoskeletal dynamics via phosphorylation of AKT. Despite its importance to biology and medicine, it is unclear how mTORC2-mediated AKT phosphorylation is controlled. Here, we identify an unforeseen principle by which a GDP-bound form of the conserved small G protein Rho GTPase directly activates mTORC2 in AKT phosphorylation in social amoebae Dictyostelium cells. Using biochemical reconstitution with purified proteins, we demonstrate that Rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 59 publications
(93 reference statements)
1
65
0
Order By: Relevance
“…This is suggested by observations of intracellular signaling patterns in cells that have been treated with Latrunculin A to disrupt the actin cytoskeleton and exhibited timescales that were of the same order as the cAMP-induced transients observed here [42,43]. Similar timescales also emerged during gradient-induced Ras reorganization or mTORC2 activation [44,45], suggesting that the transition to a lower amplitude state may be related to the organization of the chemotactic machinery. Also, recently proposed models that rely on an oscillatory actin machinery guided by an upstream wavegenerating signaling systems support this view [33,46].…”
Section: Discussionsupporting
confidence: 65%
“…This is suggested by observations of intracellular signaling patterns in cells that have been treated with Latrunculin A to disrupt the actin cytoskeleton and exhibited timescales that were of the same order as the cAMP-induced transients observed here [42,43]. Similar timescales also emerged during gradient-induced Ras reorganization or mTORC2 activation [44,45], suggesting that the transition to a lower amplitude state may be related to the organization of the chemotactic machinery. Also, recently proposed models that rely on an oscillatory actin machinery guided by an upstream wavegenerating signaling systems support this view [33,46].…”
Section: Discussionsupporting
confidence: 65%
“…However, PDK1 phosphorylation of AKT/PKBR1 requires phosphorylation by mTORC2, so absolute AKT/PKBR1 activity is dependent on mTORC2 (Liao et al, 2010). We also note input of several small GTPases in Dictyostelium (see below) that function downstream of GPCR signaling with direct positive input to mTORC2 (Khanna et al, 2016;Senoo et al, 2019;Rosel, et al, 2012;Charest et al, 2010;Liao et al, 2013).…”
Section: Fig 1 Mtor Complex Regulations In Mammalian and Dictyostelmentioning
confidence: 65%
“…Studies have shown that there is functional conservation between mammalian Rac1 and RhoA and Dictyostelium Rac1A/C and RacE, respectively (Filic et al, 2012, Wang et al, 2013a, Wang et al, 2013b. Further evidence for this was put forward in a recent study which shed light on a novel interaction between phosphorylated GDP-bound RacE or RhoA and mTORC2 kinase, resulting in downstream AKT phosphorylation in Dictyostelium and mammalian cells, respectively (Senoo et al, 2019).…”
Section: Spatiotemporal Control Of Signal Transduction Network Regulmentioning
confidence: 96%